Once Daily Valacyclovir for Reducing Viral Shedding in Subjects Newly Diagnosed with Genital Herpes - Mark G. Martens; Kenneth H. Fife; Peter A. Leone; Lynn P. Dix; Clare A. Brennan (Hindawi Limited, 2009)
Objective. Genital herpes (GH) recurrences and viral shedding are more frequent in the first year after initial HSV-2 infection. The objective of this study was to provide the first evaluation of valacyclovir 1 g once daily compared to placebo in reducing viral shedding in subjects newly diagnosed with GH. Methods. 70 subjects were randomized to receive valacyclovir 1 g daily or placebo in a crossover design for 60 days with a 7-day washout period. A daily swab of the genital/anal-rectal area was self-collected for HSV-2 detection by PCR. Subjects attended the clinic for routine study visits and GH recurrence visits. Treatment differences were assessed using a nonparametric crossover analysis. Results. 52 subjects had at least one PCR measurement in both treatment periods and comprised the primary efficacy population. Valacyclovir significantly reduced HSV-2 shedding during all days compared to placebo (mean 2.9% versus 13.5% of all days (P<.01), a 78% reduction). Valacyclovir significantly reduced subclinical HSV-2 shedding during all days compared to placebo (mean 2.4% versus 11.0% of all days (P<.01), a 78% reduction). However, 79% of subjects had no GH recurrences while receiving valacyclovir compared to 52% of subjects receiving placebo (P<.01). Conclusion. In this study, the frequency of total and subclinical HSV-2 shedding was greater than reported in earlier studies involving subjects with a history of symptomatic genital recurrences. Our study is the first to demonstrate a significant reduction in viral shedding with valacyclovir 1 g daily compared to placebo in a population of subjects newly diagnosed with HSV-2 infection.